Antibacterial Potential of Linot Honey, Yellow Honey, and Black Honey Extracts against Methicillin-Resistant Staphylococcus aureus (MRSA): Inhibition Study on Wound Infections - Unni Bayani Buchari; Mirnasari Amirsyah; Mudatsir (Gema Lingkungan Kesehatan, 2024)
The emergence of antibiotic-resistant bacteria has drawn significant attention. There is a need to develop new treatment methods using natural products that are safer for both the environment and humans. The aim of this research is to identify the phytochemical content of linot honey (Heterotrigona itama), yellow honey, and black honey, and to evaluate their in vitro antimicrobial activity against methicillin-resistant Staphylococcus aureus (MRSA). Standard qualitative methods were used to analyze the phytochemical content of the honey. The antibacterial activity of the honey was tested using the Kirby-Bauer method. Data were analyzed using one-way ANOVA and post-hoc tests. The ethyl acetate fraction of linot honey showed the highest inhibition zone against methicillin-resistant Staphylococcus aureus, with a zone of 38.67±0.30 mm. This study indicates that the ethyl acetate fraction of linot honey has high antibacterial activity against these bacteria in vitro. The study supports the use of linot honey as an alternative treatment for various bacterial skin infections.